FIRST PRINCIPAL CALCULATION : MORPHOLOGY AND ELECTRICAL PROPERTIES ANALYSIS OF Pt/GRAPHENE AS CATALYST - ANUGRAH PUTRI NAMARI (NIM : 10212072), NUNING
The increasing in energy needs and the lack of non-renewable energy sources becomes a challenge for the human being to be able to use renewable energy sources. Many scientist have been doing experiment to find the way to process the renewable energy sources in order to be applied in everyday use. One of the devices that have been developed is Fuell Cell. Fuel cell use hydrogen as energy sources . The most important reaction in fuel cell is Oxidation and reduction process. Therefore, a catalyst is needed to help the OR process. Recent study of catalyst shows that the most effective catalyst for fuel cell is Platinum. Many fuel cell have use platinum as the catalyst. However, Platinum is a rare and expensive element. Therefore, to reduce the cost of fuel cell fabrication, we need to increase the activity of platinum. In this research, we use graphene as a support material. In this research, we will study about the interaction of platinum on graphene and analyze its morphological change and electronic properties.The research conduct using Density Functional Theory (DFT). The calculation result shows that pt/graphene structure is 94% reversible and adsorption energy of H2 is 0:256eV.